"I Feel Trapped": The Tension Between Personal and Structural Factors of Social Isolation and the Desire for Social Integration Among Older Residents of a High-Crime Neighborhood. (17th February 2017) - Portacolone, Elena; Perissinotto, Carla; Yeh, Jarmin Christine; Greysen, S Ryan
Abstract: Background and Objectives: The aim of this study was to examine the factors contributing to the social isolation of older residents of a high-crime neighborhood through the in-depth examination of their lived experiences. A deeper understanding of factors contributing to social isolation can allow policymakers and health care providers to create policies and programs to alleviate the social isolation of these vulnerable and understudied individuals. Research Design and Methods: Participants were recruited through the support of the Housing Authority and Police and Fire Departments of Richmond, California, a town with a high-crime rate. Fifty-nine ethnographic interviews were conducted with 20 individuals of 58–95 years of age. Transcripts and fieldnotes were analyzed with a focus on the specific factors contributing the social isolation of participants. Results: An overarching theme of tension between personal and structural factors of social isolation and desire for social integration emerged from qualitative content analysis. A tension emerged between a longing to participate in society and the immersion in a reality so dense with obstacles that made participation in society difficult to attain. Four specific themes also emerged. Three themes demonstrated underlying factors of social isolation stemming from the personal sphere and the physical and social environment. The fourth theme illustrated participants' desire for social integration. Discussion and Implications: Findings demonstrate the salience of interventions and programs to make neighborhoods safe and accessible to older residents. Findings also suggest a need to reframe the conceptual framework for social isolation to better measure and alleviate this public health problem.